WOMEN'S EMPOWERMENT IN MICRO, SMALL, AND MEDIUM ENTERPRISES (MSMES): LITERATURE REVIEW - Nur Aisyah Fitri; Ritha F. Dalimunthe; Prihatin Lumbanraja (Musytari : Neraca Manajemen, Akuntansi, dan Ekonomi, 2024)
Through literature review, this study aims to analyze women's empowerment in micro, small, and medium enterprises. Based on the review, it can be concluded that women entrepreneurs must have a positive self-concept by increasing self-acceptance, building self-confidence, honing their skills, and establishing good relationships with others. In addition, the quality of human resources plays an important role in empowering women in micro, small and medium enterprises. This can be done by providing regular training, mentoring, and socialization on how to run a good business so that women entrepreneurs can have the ability in creativity and innovation to develop businesses at various scales both micro, small, and medium.